Augmented immune responses to a booster dose of oral cholera vaccine in Bangladeshi children less than 5 years of age: Revaccination after an interval of over three years of primary vaccination with a single dose of vaccine. Issue 7 (11th February 2020) - Chowdhury, Fahima; Bhuiyan, Taufiqur Rahman; Akter, Afroza; Bhuiyan, Md Saruar; Khan, Ashraful Islam; Tauheed, Imam; Ahmed, Tasnuva; Ferdous, Jannatul; Dash, Pinki; Basher, Salima Raiyan; Hakim, Al; Lynch, Julia; et al.
Abstract: We have earlier reported that a single dose of oral cholera vaccine (OCV) is protective in adults and children ≥5 years of age and sustained for 2 years. We enrolled participants (n = 240) from this study, between March-September 2017, over 3 years after receiving a primary single dose. Immune responses were measured in placebo group (Primary Immunization group: PI) and compared with those who received a single dose (Booster Immunization group: BI). The children were 4 to <5 years, 5 to <18 years and adults >18 years. Blood was collected at day 0 (before vaccination) and after receiving 1st and 2nd doses of OCV. Overall, the BI and PI groups showed vibriocidal antibody response after 1st and 2nd dose of vaccination in all age groups to V. cholerae O1 and O139. Young children in the BI group showed significantly higher vibriocidal antibody response two weeks after receiving the first dose as compared to PI group to LPS. Elevated plasma IgA responses to LPS after the first dose were observed among the BI group compared to the PI group among the young children. Mucosal antibody responses measured in fecal extracts showed similar increases as that of vibriocidal and LPS responses in the BI group. These results suggest a single boosting dose of OCV generated immune response in primed population >5 years of age who had earlier received OCV. However, young children who had received OCV earlier, boosting after a single dose, resulted in increased immune responses compared to the PI group. Further studies are needed to assess protection obtained from different strategies, especially for young children and to determine the numbers of primary and booster doses needed. In addition, more information is needed regarding the optimum interval between primary and booster doses to plan future interventions for cholera control. ClinicalTrials.gov Identifier: NCT 02027207.